2016
DOI: 10.1161/atvbaha.116.307132
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic NADPH Oxidase Subunit NoxO1 Promotes an Endothelial Stalk Cell Phenotype

Abstract: Objective— Reactive oxygen species generated by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases contribute to angiogenesis and vascular repair. NADPH oxidase organizer 1 (NoxO1) is a cytosolic protein facilitating assembly of constitutively active NADPH oxidases. We speculate that NoxO1 also contributes to basal reactive oxygen species formation in the vascular system and thus modulates angiogenesis. Approach and Results— A N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Although available data are not sufficient to depict a comprehensive picture of the mechanisms that allow interactions between Notch and ROS in the endothelium, there are some clues that allow some speculations. As mentioned above, Nfr2 is activated in response to oxidative stress and its modulation of Notch is well established but also a direct regulation of Notch processing enzymes by ROS has been reported . Therefore, it appears possible that the Notch pathway can be altered by Nfr2 to protect cells from endogenous or exogenous stressors, or precisely regulated, through production of H 2 O 2 in response to a physiological stimulus, by targeted oxidization of a specific Notch ligand, receptor or processing enzyme.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although available data are not sufficient to depict a comprehensive picture of the mechanisms that allow interactions between Notch and ROS in the endothelium, there are some clues that allow some speculations. As mentioned above, Nfr2 is activated in response to oxidative stress and its modulation of Notch is well established but also a direct regulation of Notch processing enzymes by ROS has been reported . Therefore, it appears possible that the Notch pathway can be altered by Nfr2 to protect cells from endogenous or exogenous stressors, or precisely regulated, through production of H 2 O 2 in response to a physiological stimulus, by targeted oxidization of a specific Notch ligand, receptor or processing enzyme.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, it has been recently reported that Nox2‐mediated ROS production promotes arterial EC specification in mouse‐induced pluripotent stem cells (miPSCs) and contributes to the angiogenic potency of transplanted miPSC‐derived EC by activating the Notch signaling . Furthermore, Brandes et al have shown that ROS act as regulators of angiogenesis by modulating the Notch signaling. In this study it has been demonstrated that LECs (lung endothelial cells) knockout for the Nox organizer protein 1 (NoxO1) exhibit attenuated Notch signaling as a consequence of a diminished NoxO1‐dependent ROS activation of the metalloprotease ADAM17.…”
Section: Crosstalk Between Notch and Rosmentioning
confidence: 90%
“…NoxO1, the homologue to p47 phox , facilitates the assembly of NADPH oxidase subunits and, therefore, promotes NADPH oxidase activation mainly through NOX1 [79]. NoxO1 −/− mice had faster retinal vascular development with less avascular retinal area at both postnatal day 5 (p5) and p7 and increased capillary density at p7 [80]. In the hindlimb ischemic-reperfusion model, NoxO1 −/− mice had faster restoration of blood flow and capillary density with increased VEGF expression in the muscles of the ischemic legs [80].…”
Section: Nadph Oxidase (Nox) In Angiogenesismentioning
confidence: 99%
“…NoxO1 −/− mice had faster retinal vascular development with less avascular retinal area at both postnatal day 5 (p5) and p7 and increased capillary density at p7 [80]. In the hindlimb ischemic-reperfusion model, NoxO1 −/− mice had faster restoration of blood flow and capillary density with increased VEGF expression in the muscles of the ischemic legs [80]. Lung ECs isolated from NoxO1 −/− mice had increased angiogenic capacity and expression of VEGFR2 and the tip cell marker, Notch ligand Delta-like 4 (DLL4) [80].…”
Section: Nadph Oxidase (Nox) In Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation